Effects of sulfur compounds on the hydrogenation and isomerization of 1-hexene over a sulfided CoMo catalyst for hydrodesulfurization. Issue 39 (5th April 2016) - Tu, Chunyan; Li, Mingfeng; Li, Huifeng; Chu, Yang; Liu, Feng; Nie, Hong; Li, Dadong
Abstract : Effects of H2 S and organic sulfides on the hydrogenation and isomerization of 1-hexene over a CoMo catalyst were systematically investigated. Abstract : The transformation of olefins is crucial to the hydrodesulfurization (HDS) of fluid catalytic cracking (FCC) gasoline. The reactivity of 1-hexene was studied over a sulfided CoMo/Al2 O3 catalyst. Effects of hydrogen sulfide (H2 S) and three organic sulfur compounds on 1-hexene transformation were also investigated. As for the hydroconversion of 1-hexene, the double-bond isomerization (ISOM) of 1-hexene proceeded readily at lower temperatures while the hydrogenation (HYD) of 1-hexene and its isomers predominated at higher temperatures. The inhibiting effect of H2 S on both isomerization and hydrogenation reactions resulted in the decline in 1-hexene HYD conversion. The saturation rate of 1-hexene increased sharply when H2 S content decreased to below 100 μg g −1 S. It was also found that thiophene (T), 2-methylthiophene (2MT) and 3-methylthiophene (3MT) strongly inhibited the hydrogenation of 1-hexene. Furthermore, the inhibiting effect on 1-hexene HYD reaction originated from H2 S generated by organic sulfide desulfurization. More isomerization products were obtained in the presence of sulfur compounds, probably attributable to the inhibition of sulfur compounds on the hydrogenation of 1-hexene and its isomers.